Methods of Implementation of Lean Production Tools in a Modern Enterprise - Marina V. VERKOVSKAYA; Ekaterina V. MENSHIKOVA; Nina V. POTEKHINA; Tatiana G. TRUBCHENKO; Anatolii N. DREVAL; Zoya V. KRINITCYNA; Oleg V. KHAZANOV (Communications of International Proceedings, 2021)
Lean production becomes the most important factor in increasing the competitiveness of enterprises and is the most effective, reliable and low-cost way to recover from the crisis. Lean production methods allow to improve the quality of products or services without capital costs. Therefore, it is necessary to define ways of introduction of lean production tools in enterprises. The article is devoted to analyze of methods of implementation of lean production tools in companies of different branches of economy. The following objectives are set: to identify the factors that determine the successful implementation lean production tools; to determine the reasons of ineffective introduction of lean manufacturing in Russia; to develop a methodology of implementation of lean production in companies of different branches of economy. The research was carried out at Russian enterprises of various branches of economy (retail trade, sphere of services, construction). The results showed that the developed methodology can be used by the heads of organizations to eliminate losses in the production process. It is a practical guide that explains how to use a set of lean manufacturing tools to achieve a particular goal in any sector of the economy.
Keywords: Lean production; enterprise management concept; loss reduction; service sector.